Archaeological and Visual Sources of Meditation in the Ancient Monasteries of Kuca. - Howard, Angela (Studies in Asian art and archaeology., 2014)
In Archaeological and Visual Sources of Meditation in the Ancient Monasteries of Kuča, Angela F. Howard and Giuseppe Vignato use diverse methodological approaches from archaeology, art history and religious studies to reconstruct monastic life and practices in the rock monasteries on the northern Silk Route (ca. 200-650).